THE EFFECTIVENESS OF USING WORDAISY MODULE TO IMPROVE NUMBER OF VOCABULARY AMONG YEAR THREE PUPILS - Anis Zafira Baharudin; Mohamed Amin Embi; Harwati Hashim (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The 21st Century Learning has become an amazing benchmark for the education system in the most country of all around the world as it promotes a new chapter of learning experiences among the learners. This new and advanced learning is believed to return more benefits to the learners as it highlights the importance of creativity, higher order thinking and reasoning skills. Not to forget, the 21st Century Learning demands integration of technology in the classroom so that the learning experiences will be more engaging and interesting in line with the super advanced technology that takes place in our daily life. In Malaysia, the education system is transforming into a better version. The English language has been given the same highlight as an important language to be mastered by all learners. However, due to its position as the second language in this country, there are lots of learners who are still struggling to comfortably learn and use the language due to many underlying factors. One of the main factors is the lack of vocabulary. Therefore, it is a must to discover the best method to help the learners widen their range of vocabulary. Therefore, this study will investigate the effectiveness of using the Wordaisy Module in expanding learner’s number of vocabularies. This study was conducted with 20 pupils in a suburban school in Selangor. The data was collected via interviews, questionnaires and tests’ scores. The findings showed that majority of the respondents agreed that the module did help them to acquire vocabulary. Therefore, it is hoped that the invention of Wordaisy Module will help to improve pupils’ mastery of English vocabulary in ESL classroom.